Fourfold increase in photocurrent generation of Synechocystis sp. PCC 6803 by exopolysaccharide deprivation - Wey, Laura T.; Wroe, Evan Indigo; Sadilek, Viktor; Shang, Linying; Chen, Xiaolong; Zhang, Jenny Z.; Howe, Christopher J. (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Photosynthetic microorganisms, including algae and cyanobacteria, export electrons in a light-stimulated phenomenon called 'exoelectrogenesis'. However, the route(s) by which electrons reach an external electrode from the cell remain(s) unclear. For the model cyanobacterium Synechocystis sp. PCC 6803, it has been established that electron transfer does not depend on direct extracellular electron transfer by type IV pili. However, the role of the exopolysaccharide matrix in which cells are embedded has not been investigated. We show that a Synechocystis mutant with substantially reduced exopolysaccharide production has a four-fold greater photocurrent than wildtype cells. This increase is due in part to increased adhesion of exopolysaccharide-deficient cells to electrodes. Stirred system experiments reveal that a substantial portion of the photocurrent depends on an endogenous diffusible electron mediator, supporting indirect extracellular electron transfer as the bioelectrochemical mechanism of exoelectrogenesis. These findings will be important in harnessing exoelectrogenesis for sustainable electricity generation in biophotovoltaic devices.